Investigation on the decomposition mechanism and kinetic behavior of 5-aminotetrazole with metal oxide produced by added coolants. (1st November 2021) - Cao, Chengyang; Liu, Huimin; Zhang, Dan; Zhu, Kai; Li, Aijun; Wang, Linling; Hu, Hongyun
Highlights: Al2 O3 and MgO can catalyze the decomposition of 5-aminotetrazole at high temperature. Thermokinetic characteristics of 5-aminotetrazole with Al2 O3 and MgO were explored. Decomposition mechanism of 5-aminotetrazole with Al2 O3 and MgO were revealed. Abstract: Coolant additives are commonly used to offset the excessive combustion temperature of 5-aminotetrazole (5-AT) based solid propellants. However, the discrepancy of the burn-rate reduction by different coolants has been observed, restricting the precise control of 5-AT propellant's combustion behavior. The focus of the current study is the effect of two metal oxides (Al2 O3 and MgO), produced by the endothermic decomposition of coolants (Al(OH)3 and MgCO3 ), on the decomposition mechanism and kinetic behavior of 5-AT. Results showed that these two additives impact the decomposition of 5-AT above 310 °C, focusing on the formation and decomposition of condensation products (melamine, melem, and melon-like). It revealed that the polymer layer thickness increased by Al2 O3 but decreased with MgO, which directly influenced the gas evolution process and heat transfer process. Kinetic calculation using the advanced Vyazovkin method and standard Criado method confirmed the catalytic decomposition of condensation products over the metal oxides' surface. The reaction model changed from the reaction order model (Fn) to the geometrical model (Rn). Scheme and mechanism of the decomposition of 5-AT at separated stages were proposed. The findings of this study could contribute to understanding the burn-rate reduction mechanism of coolants and benefit the design of composite coolants used in 5-AT based propellants.